Botulinum toxin A (BT-A) versus low-level laser therapy (LLLT) in chronic migraine treatment: a comparison - Luana Mazzacoratti Loeb; Rebeca Padrão Amorim; Maria da Graça Naffah Mazzacoratti; Fulvio Alexandre Scorza; Mario Fernando Prieto Peres (Arquivos de Neuro-Psiquiatria)
ABSTRACT The aim of this work was to evaluate patients with chronic migraine treated with botulinum toxin A (BT-A) and compare this with low level laser therapy (LLLT), referencing: pain days, pain intensity, intake of drugs/self-medication, anxiety and sleep disorders. Methods: Patients were randomized into two groups: BT-A group (n = 18) and LLLT group (n = 18). Each patient kept three pain diaries: one before (baseline) (30 days), one during treatment (30 days) and one after the post-treatment phase (30 days). Repeated ANOVA plus the Bonferroni post-test, Student's t test, and factorial analysis were applied, and p < 0.05 was accepted as significant. Results: Our data showed that both treatments were able to reduce headache days, acute medication intake and decrease the intensity of pain. Anxiety was reduced in the BT-A group, while sleep disturbance was reduced in the LLLT group. Conclusion: Our data showed that both treatments can be used to treat chronic migraine, without notable differences between them.